Occurrences of (non)-separation of languages in Teletandem - GARCIA, Daniela Nogueira de Moraes; DE OLIVEIRA , Victor César; SANTOS , Douglas Cunha dos (The ESPecialist, 2022)
Telecollaboration has allowed access to peoples and languages, crossing geographical barriers and providing significant experiences to build language knowledge, develop autonomy, and intercultural competence. Teletandem, a context that provides for bilingual communication between learners of different languages using software such as Skype and Zoom, has facilitated significant pedagogical practices. After the interaction, a teacher/researcher/mediator conducts the mediation sessions with the group of participants to promote sharing of experiences and to encourage reflection. The present work, under a qualitative methodology, focuses on data from mediation sessions with Brazilian students conducted in 2016. Thus, based on theories of telecollaboration, tandem, and teletandem, we examine occurrences of non-separation of languages in interactions, reported by the students in mediation sessions, to understand it and aiming to reinforce procedures and alignment as a whole. The results point to the imbalance established by mixing languages, which can endanger the actions between peers, generating discomfort and interfering in the other principles, reciprocity and autonomy. The importance of conducting mediation sessions is pointed out as an alignment context and also the mediator's role in supporting and enhancing the experience among peers.